التغيير السياسي والعدالة الانتقالية في تونس في أعقاب 2011 توطيد الديمقراطية في مواجهة المصالحة الاقتصادية - بن شعبان, رمضان (revue mofakir, 2018)
Addressing the issue of political change toward a democratic system that takes into account a range of critical policy choices taken by active actors, to allow completion of the strengthening of institutions, and make it more democratic. Within this context, Tunisia appears the first Statein the Arab world, which has been an abnormal case among democracy scholars, where a gesture of political change. reflected in the fourteenth of January 2011, after weeks of protests ended the authoritarian regime "of Zine El Abidine Ben Ali." As a result, one of the strongest challenges of the stage of political change, the promotion of a range of democratic process mechanisms, clearly embodied in the transitional justice system that sparked huge debate over it, and beginning to talk about its failure to give a project of economic reconciliation which can be considered by many analysts as a key to the democratic process.